Smuggling of Money and (or) Monetary Instruments Through the Prism of Judicial Decisions - Natal'ya E. Panfilova (Сибирское юридическое обозрение, 2017)
The article is devoted to the study of a relatively new crime composition art. 200.1 of the Criminal Code of the Russian Federation “Smuggling of money and (or) monetary instruments”, criminalized in 2013. Based on the available judicial practice, the objective and subjective elements of the crime are analyzed. The main task of the research is to determine whether the criminalization of this socially dangerous act corresponds to the real goals of its criminalization. The main attention is paid to the subject, methods and appointed penalties for this crime. On the basis of the law enforcement practice, a criminological portrait of the perpetrators of this crime was revealed. The Author comes to the conclusion that such goals of criminalization of this socially dangerous act, as counteraction to the financing of terrorism, combating the legalization of money, are practically not achieved. Recommendations are offered to eliminate this situation.